Association between cardiometabolic index and frailty among patients with diabetes mellitus: a cross-sectional study - Wei, Yi; Yu, Jiangyi (Frontiers in Nutrition, 2024)
Background: Cardiometabolic index (CMI) is a novel marker that can assess metabolic status.Studies have found that people with diabetes mellitus (DM) are at high risk of developing frailty.However, there is a lack of evidence between CMI and the risk of frailty in patients with DM.Therefore, the aim of this study was to investigate the association between CMI and frailty in patients with DM.Methods：Weighted multivariate logistic regression was conducted in this study to explore the association between CMI and frailty status in patients with DM. In addition, subgroup analyses and interaction analyses were conducted to assess heterogeneity between different subgroups.Subsequently, restricted cubic spline (RCS) was also used to test for non-linear relationships.Results：This study ultimately included 2,761 patients with DM. Weighted multivariate logistic regression showed that, after adjusting all covariates, an increase in the level of CMI was associated with an increased risk of being in a frailty status in patients with DM (OR=1.12, 95% CI=1.04-1.22, P=0.005). Dividing CMI into tertiles, the risk of frailty in patients in the highest tertile (Q3) was higher than that of patients in Q1 (OR=1.56, 95% CI=1.18-2.07, P=0.002). The non-linear relationship between CMI and the risk of frailty in DM patients was further confirmed by RCS analysis.Conclusion：This study found that the higher the CMI, the higher the risk of frailty in DM patients.Maintaining a healthy low-fat dietary pattern and properly controlling blood lipid levels may reduce the risk of frailty in people with DM.